2020
DOI: 10.1186/s12883-020-01855-5
|View full text |Cite
|
Sign up to set email alerts
|

Migraine, attention deficit hyperactivity disorder and screen time in children attending a Sri Lankan tertiary care facility: are they associated?

Abstract: Background: Headache and Attention Deficit Hyperactivity Disorder (ADHD) are two relatively common, neuropsychiatric conditions seen in children. Recent studies have shown an association between these two disorders, which are otherwise distinct conditions. This study aims to assess the association between migraine and ADHD, as well as the association between screen-time and these two conditions, among children attending a Sri Lankan tertiary care facility. Possible associations will have important implications… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 39 publications
3
23
0
Order By: Relevance
“…The confounders were included based on existing literature. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The statistical analyses were performed using SPSS statistics software (version 26; IBM Corp., Armonk, New York, United States). The level of significance was set at 0.05.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The confounders were included based on existing literature. [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31] The statistical analyses were performed using SPSS statistics software (version 26; IBM Corp., Armonk, New York, United States). The level of significance was set at 0.05.…”
Section: Methodsmentioning
confidence: 99%
“…No clear definition of screen time, or which devices it includes, is found in existing studies and literature, but the common denominator is time spent on screen-based electronics. [22][23][24][25] According to a large study including 2,000 young Americans in 2010, the average 8-to 10-year-old spent nearly 5.5 hours a day in front of a screen, 11-to 14year-olds spent > 8 hours a day while 15-to 18-year-olds spent > 6 hours daily. 26 American Academy of Pediatrics (AAP) recommends that the child's total entertainment screen time is limited to a maximum of 2 hours per day.…”
Section: Introductionmentioning
confidence: 99%
“…Parallel to the rise in screen media use in adults, it is expected that screen device use and related health adversities in children have also risen. Recent studies have reported associations between high screen time and migraine and behavioural problems among older children in Sri Lanka [ 14 , 15 ]. However, the conformity to international recommendations on screen time among preschool children in Sri Lanka has not been studied.…”
Section: Introductionmentioning
confidence: 99%
“…Though a causal association cannot be maintained, a high prevalence of ADHD symptoms has been described in children and adolescents suffering from migraine ( 48 , 49 , 69 ) ( Table 1 ). Arruda et al ( 48 ) showed a significant higher prevalence of ADHD in children with migraine compared with control subjects.…”
Section: Resultsmentioning
confidence: 99%